EXPRESSION OF MORAL CRITERIA IN IBN SINA’S PHILOSOPHICAL STORIES THROUGH ARTISTIC IMAGES (TAMADDUN NURI JURNALI, 2024)
The article describes some of the shortcomings of human character and the need to protect yourself from such shortcomings and avoid them as much as possible. Ibn Sina also lists these shortcomings in his philosophical stories and describes the ways and reasons for getting rid of such shortcomings.